The Impact of Coronavirus Disease 2019 on the Disease Pattern of Oral and Maxillofacial Surgery Inpatients: A Comparative Study - Pu, Jingya Jane; McGrath, Colman Patrick; Leung, Yiu Yan; Choi, Wing Shan; Yang, Wei-fa; Li, Kar Yan; Su, Yu-xiong (Frontiers in Medicine, 2021)
Objective: Oral and maxillofacial surgery (OMFS) is a high-risk specialty involving airway and aerosol-generating procedures, which is potentially of more risk in the era of coronavirus disease 2019 (COVID-19). We aimed to identify the impact of COVID-19 on the disease pattern of OMFS inpatients and surgeries under general anesthesia in a comparative study. Materials and Methods: We reviewed the admission and operating theater records of OMFS patients from Jan 1 to Aug 31 in 2020 and 2019. The total number of cases, presenting disease patterns, and proportion of essential and non-essential medical services were compared between 2020 and 2019. Results: There were 664 admissions and 356 general anesthesia surgical procedures included in this study. Both admission and surgery numbers were significantly reduced in 2020, compared with 2019 (p = 0.012 and 0.007, respectively). The proportion of malignancy cases increased significantly, whereas that of cleft lip and palate and temporomandibular disorder (TMD) decreased. There was a significant increase in the proportion of essential services compared with non-essential services in 2020 compared with 2019. Conclusion: Our results first reported the epidemiological data of the impact of COVID-19 on OMFS disease pattern in a comparative study. The change of disease pattern and caseload will have a long-term impact on OMFS patient care, education, and training during the pandemic. Our paper provides evidence for health policy makers to consider the relocation of medical resources and optimization of medical education and services.